Formal Language Theory (FLT): Refining the Chomsky Hierarchy: Exploring the Applications and Refinements of Formal Language Theory (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Formal language theory (FLT) is an important part of the mathematics of computers andcontains an extensive corpus of research findings and theorems on rule-based generative rulesystems (GRS). Format Language Theory (FLT) has a wide range of applications, including computerprograms, music, visual patterns, animal vocalizations, RNA structure, and even dance. In this paperdiscuss the Chomsky Hierarchy, Languages With A Slightly Sensitive Context, CognitiveComplexity, Languages Used In Subregular Conventions.